Stephano Guzzini - The History of the CEU
Interview with Prof. Stephano Guzzini about the history of the CEU. Questions are asked by Béla Nové. Guzzini brings forward the experience of moving CEU programs and departments from Prague, Czech Republic to Budapest, Hungary. He provides a detailed description of the Department of International Relations and European Studies, explains how the program developed as a cross-disciplinary program and recounts the main developments and the future plans of the Department.